The Effect of Carboxymethyl Cellulose (CMC) Addition on The Quality of Biodegradable Plastic from Corn Cob - Ihsan, M. Bayu; Ratnawulan, Ratnawulan (Pascasarjana, Mataram University, 2024)
This study aims to determine the effect of CMC addition on thickness, tensile strength, elongation and biodegradation of biodegradable plastic from corn cob starch. In this study, the addition of Carboxymethyl Cellulose which plays a role in increasing the tensile strength of biodegradable plastics. This research was conducted in 2 stages. The first stage is varying CMC as much as 20%, 30%, 40%, 50% and 60% (w/b starch) and the second stage is mixing corn cob starch as much as 2 grams with CMC 20% - 60% w/b starch. The test results showed that the addition of CMC concentration of 20% w/w with corn cob starch mixing material had an effect on increasing the tensile strength value and decreasing the elongation value of the plastic. The addition of CMC concentration as much as 20%-60% w/b starch with corn cob starch blending material has an effect on increasing the percent weight loss of biodegradable plastics